Analisis Perbandingan Metode EOQ POQ Dalam Perencanaan Pengendalian Persediaan Retail Toko A - Lopenzo, Sanrio Febry; Jesen; Syara Nasution, Rivara (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Universal, 2024)
Toko A is a company that buys supplies in large quantities from suppliers and resells them to consumers in smaller amounts therefore inventory management is very important. Toko A ways of managing inventory in the warehouse are still based on intuition. The warehouse gets overloaded sometimes due to stocks that are way too many to be kept causing items to be damaged such as for shirts and shoes making it lose its value. The purpose of this research is to find the best method of inventory planning and control based on the smallest Total Inventory Cost between the method that is being applied by the company currently with Economic Order Quantity (EOQ) and Period Order Quantity. The result shows that the best method for managing inventory is EOQ which saves IDR25.068.334 for the shirt category and IDR21.909.229 for the shoes category in 2021. The best method to manage inventory from January until March of 2022 is also EOQ which saves IDR1.077.434 for the shirt category and IDR254.632 for the shoes category.